Digital Marketing dan Kualitas Produk Terhadap Loyalitas Konsumen pada Produk Vicy Cake Kambang Pesisir selatan - Vobi Arjunda; Maria Magdalena (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The key to long-term marketing success, which is the dream of all marketers, is creating strong and close relationships with consumers. The aim of this research is to determine the influence of digital marketing and product quality on consumer loyalty. Through the questionnaire method with samples using the Slovin formula, there were 60 respondents. Meanwhile, the population used in this research is all Vicycake consumers from January to June 2023. Hypothesis testing via the t test (Partial Test) shows that digital marketing and the quality of the products studied are proven to significantly influence consumer loyalty. the results shown from the t test (Partial Test) digital marketing variable have a t-count greater than the t-table, this can be interpreted that HO is rejected and H1 is accepted and the product quality variable has a t-count greater than the t-table, this can be means that HO is rejected and H2 is accepted.